Development of Critical Thinking and Collaboration Skills in Science Learning at Elementary School: A Case Study - Dita Purwinda Anggrella; Luluk Nurjanah; Ahmad Kamal Sudrajat (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractIn the era of industry 4.0, students are faced with the complexity of a changing world and the demand to develop relevant skills, one of which is critical thinking and collaboration skills. However, educators face difficulties in developing and integrating these skills into learning practices. This study aims to investigate the difficulties of teachers in developing critical thinking and collaborative skills in science learning. The research method used is a case study. Data collection was conducted at SD Aisyiah Surya Ceria, Karanganyar, Central Java through interviews with thematic teachers of grade III, students, and vice principals of curriculum. The results of the study indicate that the difficulties experienced by teachers in developing critical thinking and collaboration skills are related to student conditions, namely student thinking skills and learning characteristics. While the supporting factors are school policies, facilities, innovative learning models and mastery of information technology for the learning process.Keywords: critical thinking skills, collaboration, science learning. AbstrakDi era industri 4.0, siswa dihadapkan pada kompleksitas dunia yang terus berubah dan tuntutan untuk mengembangkan keterampilan yang relevan, salah satunya adalah keterampilan berpikir kritis dan kolaborasi. Namun demikian, para pendidik menghadapi kesulitan dalam mengembangkan dan mengintegrasikan keterampilan tersebut dalam praktik pembelajaran. Penelitian ini bertujuan untuk menginvestigasi kesulitan-kesulitan guru dalam mengembangkan kemampuan berpikir kritis dan kolaboratif dalam pembelajaran IPA. Metode penelitian yang digunakan adalah studi kasus. Pengumpulan data dilakukan di SD Aisyiah Surya Ceria, Karanganyar, Jawa Tengah melalui wawancara dengan guru tematik kelas III, siswa, dan wakil kepala kurikulum. Hasil penelitian menunjukkan bahwa kesulitan yang dialami guru dalam mengembangkan keterampilan berpikir kritis dan kolaborasi berkaitan dengan kondisi siswa, yaitu kemampuan berpikir dan karakteristik belajar siswa. Sedangkan faktor pendukungnya adalah kebijakan sekolah, fasilitas, model pembelajaran yang inovatif dan penguasaan teknologi informasi untuk proses pembelajaran. Kata kunci: keterampilan berpikir kritis, kolaboratif, pembelajaran IPA.